Smartphone Use for Work during Personal Activities: An Investigation into Work-Life Conflict - Sheilla Lim, Omar Lim; Elim, Wong; Ross Azura, Zahit (UNIMAS Publisher, 2022)
This quantitative study investigates the impact of smartphone use for work and time-based work interference with leisure (WIL) on work-life conflict among 123 private-sector workers in Kuching, Sarawak. Analyses of Pearson Correlation Coefficients were carried out. The findings support previous research which suggests using smartphones for work after hours can lead to conflicts between employees' work and personal lives. Furthermore, the findings show that work-life conflict is compounded by time-based work interferences with leisure (WIL). These findings have ramifications for policies and procedures surrounding work-related smartphone use and the amount of time spent on specific tasks during off-work hours, which could negatively impact employees' work-life balance.